Comparative Transcriptional Analysis of Pulmonary Arterial Hypertension Associated With Three Different Diseases - Wang, Wei; Jiang, Zhenhong; Zhang, Dandan; Fu, Linghua; Wan, Rong; Hong, Kui (Frontiers in Cell and Developmental Biology, 2021)
Pulmonary arterial hypertension (PAH) is a severe cardiovascular disorder with high mortality. Multiple clinical diseases can induce PAH, but the underlying molecular mechanisms shared in PAHs associated with different diseases remain unclear. The aim of this study is to explore the key candidate genes and pathways in PAH associated with congenital heart disease (CHD-PAH), PAH associated with connective tissue disease (CTD-PAH) and idiopathic PAH (IPAH). We performed differential expression analysis based on a public microarray dataset GSE113439 and identified one thousand four hundred forty-two differentially expressed genes, of which 80.3% were upregulated. Subsequently, both pathway enrichment analysis and protein-protein interaction network analysis revealed that the ‘Cell cycle’ and ‘DNA damage’ processes were significantly enriched in PAH. The expression of seven upregulated candidate genes (EIF2AK2, TOPBP1, CDC5L, DHX15 and CUL1-3) and three downregulated candidate genes (DLL4, EGFL7 and ACE) were validated by qRT-PCR. Furthermore, cell cycle related genes Cul1 and Cul2 were identified in pulmonary arterial endothelial cells (PAECs) in vitro. The result revealed an increased expression of Cul2 in PAECs after hypoxic treatment. Silencing Cul2 could inhibit over proliferation and migration of PAECs in hypoxia. Taken together, according to bioinformatic analyses, our work revealed that ‘Cell cycle’ and ‘DNA damage’ processes related genes and pathways were significantly dysregulated expressed in PAHs associated with three different diseases. This commonality in molecular discovery might broaden the genetic perspective and understanding of PAH. Besides, silencing Cul2 showed an protective effect in PAECs in hypoxia. The results may provide new treatment targets in multiple diseases induced PAH.